Pemeliharaan Lingkungan Rawan Longsor dan Erosi Melalui Kegiatan Reboisasi Bibit Tanaman Berdaya Jual Di Desa Kekait - Aris Doyan; Ramilia Laksmi Utari Umar; Septian Ananda Saputri; Azzumar Wirahadi; Anak Agung Istri Dhika Dharma Putri; Muhammad Ilham Januarta; Annisa Annisa; Jahria Jahria; Ni Nyoman Sugiartini; Nur Ulla Azizati Rohima; Tasya Marwah Salsabilla; Tia Safira; Windy Aulia; Yustika Aprilia (Unram Journal of Community Service, 2022)
The University of Mataram Integrated Real Work Lecture (KKN) in 2021, is one of the required courses as a requirement for undergraduate graduation for FKIP University Mataram students. This Integrated Community Service Program is also known as the New Normal Era of Community Service, where its implementation must pay attention to a series of protocols to prevent the spread of the corona virus 2019. In the Integrated Community Service Program which was carried out in Kekait Village, Gunungsari District, West Lombok Regency, students are expected to be able to explore the problems and potential of the village. in terms of disaster and help a group of villagers build Kekait village as a Disaster Response Village. Basically, this Kekait village has been known as a producer of the purest palm sugar and guaranteed authenticity in the province of West Nusa Tenggara. However, behind the success of a business that is still as limited as a home-industry, the spread of the corona virus, the lack of domestic and international visitors, the failure of the typical kekait durian harvest, the rainy season that continues to pour regularly, the river water is increasing, and the climbing is getting worse. steepness is an urgent issue that hinders the development of the potential of Kekait village. Based on this, the Kekait Village Integrated Community Service Group in 2021 has the title Disaster Response Village: Maintenance of Landslide and Erosion-Prone Environments Through Reforestation Activities for Selling Plant Seeds while still utilizing the entrepreneurial and tourism potential above as an additional work program for the Kekait Village Integrated Community Service group